THE INFLUENCE OF BEET ROOT PLANTING QUALITY ON THE YIELD OF SUGAR BEET SEEDS - Lapenko, H. O.; Lapenko, T. H.; Marenych, M.V.; Kuzmenko, O.I. (Scientific Progress & Innovations, 2019)
Planting sugar beet stecklings with planting machine is one of the stages in the technological process of producing elite seeds. The analysis of the experience of using planting units for planting stecklings showed a number of disadvantages: poor quality of planting stecklings without spacing stability and the absence of parameter control; unregulated applying nutrients and granules of water preservation to the roots, which negatively affect the development of plants. The aggregate having openers of the planting device has been designed, where the system of supplying the spray of nutrients and growth stimulator is envisaged. The tech-nological process is conducted in the following way: during the movement of equilateral triangles of the planting cones mechanism the root is planted in the soil. To eliminate the drawbacks while planting steck-lings, the openers of the planting device for the roots having the diameter of 50–120 mm were designed. Ow-ing to them free falling roots in the soil is ensured and their lifting together with the cone to the soil surface is prevented. The research has shown that root plant spacing depends on the angular and forward velocities of the device. The draft resistance of furrow openers and soil compaction depend on the furrow width and depth and the distance between the axes of quadrangles and the unit of rear compaction wheels. Improving the planter, taking into account biological peculiarities of plant development, meeting the requirements of energy saving and economic expediency was proved. The technological parameters of the aggregate and the expediency of planting sugar beet roots for seeds with the following spacing have been substantiated: 40–70 cm and 50–60 cm. The rotational planting unit with planting cones for ensuring the quality of planting sugar beet stecklings has been adopted. It has been confirmed by the research, that plant spacing of roots is regulated by changing angular and forward velocities of the unit, which is envisaged by: - changing the star with different number of tines on the reducing gear of drive shaft; - changing forward (operating) velocity of tractor. The results of the research can be used while modernizing the existing and designing new planting machines for planting sugar beet stecklings to obtain elite seeds in agro – industrial complex of Ukraine.